Indonesia Journal Social Work Vol.6 No.1 Tahun 2022: PENGEMBANGAN TEKNOLOGI PELATIHAN KEWIRAUSAHAAN BAGI PELAKU UMKM BERBASIS PERTUKARAN PELAKU USAHA (PERKASA) DI DESA PASANGGRAHAN KECAMATAN KASOMALANG KABUPATEN SUBANG - Hafidz Fattahurahman Pramadia; Dwi Yuliani; Decky Irianti (Politeknik Kesejahteraan Sosial Bandung, 2022)
Training technology based on the exchange of business actors is a development of training technology. This exchange-based training technology aims to increase the capacity of individuals and groups. This training technology results from a combination of training and comparative studies. This study aims to analyze the results of the implementation of training technology based on the exchange of business actors in Pasanggrahan Village, Subang Regency. The method used in the research is qualitative research with the Participation Action Research (PAR) method. The targets observed in this study are MSME actors. The MSMEs involved are MSMEs that have potential and are starting their business (at the middle level). The result of this study is that there is an changed/efective from the implementation of exchange-based training technology for business actors, including increasing the knowledge capacity of business actors in developing their business, the occurrence of cooperation between MSME actors, and adding insight to develop the business they have to be more advanced. Training based on the exchange of business actors can be one of the enrichments that can be used as an alternative to improving training technology and can be an interesting method in the development of social work practice science with the community.